A Kennecott Story : Three Mines, Four Men, and One Hundred Years, 1887-1997 - Hawley, Charles Caldwell, 1950- (Book collections on Project MUSE., 2014)
"While copper may seem less glamorous than gold, it may be far more important. Copper proved vital to the industrial revolution and indispensable for the electrification of America. Kennecott Copper Corporation, at one time the largest producer of copper in the world, thus played a key role in our economic and industrial development. This book recounts how Kennecott was formed from the merger of three mining operations (one in Alaska, one in Utah, and one in Chile), how it led the way in mining technologies, and how it was affected by the economy and politics of the day. As it traces the story of the three mines, the narrative follows four mining engineers<m>men whose technological ingenuity was responsible for much of Kennecott's success. Accounts of the Guggenheims<m>under whom the mines were united<m>and other investors are also woven into the text. Without their funding, the infrastructure necessary for the mining operations may not have been built. (The railroad required for the Alaska mine alone cost more than three times what the United States had paid to buy all of Alaska only forty-five years prior.) As a geologist with first-hand knowledge of mining, author Charles Hawley aptly describes the technological workings in a way that both geologists and the general reader will appreciate. Through engaging stories and pertinent details, he places Kennecott and the copper industry within their historical context and also allows the reader to consider the controversial aspects of mineral discovery and sustainability in a crowded world where resources are limited."--